Abundance and Distribution of Microplastics in the Waters of Koroe Onowa Village, Wakatobi Regency - Basriah, Basriah; Afu, La Ode Alirman; Emiyarti, Emiyarti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The waters of Koroe Onowa Village, Wakatobi Regency, are at risk of plastic waste contamination due to human activities on land that are carried by currents into the waters. Plastic waste is very dangerous for the health of the aquatic environment, especially marine biota, because the accumulation of microplastics over a long period of time can interfere with the respiratory and digestive tracts of marine biota, and has the potential to harm human health. For this reason, research on microplastics in these waters is needed. This study aims to analyze the abundance and distribution of microplastics in the waters of Koroe Onowa Village. Microplastic sampling was carried out using a modified plankton net method, which was then identified based on the type of microplastic. The results of the study showed that there were four main types of microplastics identified, namely fragments, films, fibers, and pellets, with an abundance ranging from 3.2 to 8.86 particles per liter. Station III, which is a coastal tourism area with dense human activity, showed the highest abundance value, namely 8.86 particles/liter. The results of this study provide an initial overview of the threat of microplastic pollution in the waters of Koroe Onowa and form the basis for better monitoring and waste management efforts in the area, as well as the need for mitigation measures to protect marine ecosystems and ensure the sustainability of coastal resources.